THE SOCIOPRAGMATIC DESCRIPTION OF SPEECH IN ENGLISH AND UZBEK DRAMA - Jo`rayeva Sabina (TADQIQOTLAR, 2025)
Abstract: This article explores the sociopragmatic features of speech in English and Uzbek drama, focusing on how social norms, cultural expectations, and pragmatic conventions shape characters’ linguistic behavior. By analyzing selected plays from both traditions, the study investigates speech acts, politeness strategies, forms of address, turn-taking, and pragmatic implicatures, revealing how playwrights encode social roles, power relations, and interpersonal dynamics within dialogue. The research demonstrates that English drama often employs indirectness, hedging, and subtle conversational cues to reflect individualism and social hierarchy, whereas Uzbek drama emphasizes honorifics, culturally rooted expressions, and community-oriented communicative practices, reflecting collectivist values. Through a comparative approach, the article highlights both universal and culturally specific aspects of dramatic speech, offering insights into the intersection of language, society, and literary art. The findings contribute to a deeper understanding of cross-cultural pragmatics, dramatic discourse analysis, and the role of sociocultural norms in shaping linguistic interaction in literature.